Preliminary Data to Composition of Zooplankton in the Khe The Stream, My Son Sanctuary, Quang Nam Province - Nam, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
The zooplankton samples were collected in 30 collecting sites from 22 th August to 10 th September and from 17 th October to 05 th November 2016. Investigation of species compositon of zooplankton in the Khe The stream, My Son Sanctuary, Quang Nam province was identified 36 species belonging to 22 genera of 13 families, 5 orders, 2 classes (Eurotatoria, Crustacea), 2 phyla (Rotatoria, Arthropoda). In particular, Rotatoria was by far the most popular with 20 species, accounting for roughly 55.6%, compared to the figure of Arthropoda was 16 species, occupying approximately 44.4%. The density of zooplankton at the sampling sites averaged 11,945 individuals/m 3 , from 5,000 to 25,000 individuals/m 3 in dry season; averaged 8,500 individuals/m 3 , from 5,000 to 16,667 individuals/m 3 in rainy season. The Shannon-Weiner (H') diversity index at the study sites averaged 1.84, from 1.44 to 2.58 in dry season; averaged 1.66, from 0.72 to 2.45 in rainy season.